2011
DOI: 10.1501/vetfak_0000002468
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, pathological and immunohistochemical findings of bovine cutaneous papillomatosis

Abstract: Summary: Bovine cutaneous papillomatosis caused by a bovine papillomavirus, is a common skin disease in Turkey. The aim of the present study was to describe the clinical, histopathological and immunohistochemical aspects of naturally occurring bovine cutaneous papillomatosis. A total of 82 Holstein cattle (9.5%), aged between 5 and 24 months, were diagnosed as cutaneous papilloma by clinical examination. The percentage of papilloma and papillomatosis in male and female was found in 7.3% and 14.8%, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…This study showed that the severity of Ki67-positive cells is very high in malignant epithelial tumors than the benign one. These results are matched with the findings of [21] who found that Ki67 expression is higher in aggressive and recurring BCCs. Additionally, the highest Ki67 expression found in SCC, particularly in poorly differentiated SCC, confirms that its aggressive behavior is at least partly due to enhanced cell proliferation [22].…”
Section: Discussionsupporting
confidence: 90%
“…This study showed that the severity of Ki67-positive cells is very high in malignant epithelial tumors than the benign one. These results are matched with the findings of [21] who found that Ki67 expression is higher in aggressive and recurring BCCs. Additionally, the highest Ki67 expression found in SCC, particularly in poorly differentiated SCC, confirms that its aggressive behavior is at least partly due to enhanced cell proliferation [22].…”
Section: Discussionsupporting
confidence: 90%